Analyzing interacting phenomena: Word order and negation in Basque - Crowgey, Joshua; Bender, Emily M. (Proceedings of the 18th International Conference on Head-Driven Phrase Structure Grammar, 2011)
We explore the interaction of sentential negation and word order in Basque using a smallexperimental implemented grammar based on the Grammar Matrix (Bender et al., 2002, 2010) to test theanalyses. We find that the analysis of free word order (Fokkens, 2010) provided by the GrammarMatrix customization system can be adapted to handle the Basque facts, and that the constructionalapproach taken in that analysis supports the integration of negation.